STRATEGI POSITIONING PRODUK UNTUK MENINGKATKAN PENJUALAN MELALUI RESELLER OLEH UMKM ELIBED - Erna Diana Yanti; Nanda Juwita Putri; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Jurnal Pijar, 2023)
A successful positioning strategy will create a customer-focused value proposition. A product positioning strategy is a product strategy, part of a marketing strategy. Strategy is needed against the background of the current situation with many similar products that can lead to increasingly fierce competition. The goals of a company must be achieved properly, the company must use the right positioning strategy in order to compete with competitors. This article aims to determine the effectiveness of the product positioning strategy to increase sales through resellers implemented by the Elibed business. The data used by the author in this article is a type of qualitative data. The data sources obtained are secondary and primary data. The method used by the author is Observative with a SWOT analysis approach. The techniques used in data collection are : Observation, interviews, documentation, and literature study with SWOT analysis. The results of the SWOT analysis show that the sales strategy only through resellers faces various threats, but Elibed has strengths from an internal perspective. The strategy that can be done to increase sales of Elibed MSMEs is to take advantage of strengths in terms of internal through long-term opportunities with a diversification strategy (Product or Market).